Germination, Attachment and Development of Striga hermonthica (Del.) Benth Induced by Host and Non-host Crops (University of Khartoum Journal of Agricultural Sciences, 2023)
Striga hermonthica (Del) Benth is a semi-parasitic weed thatreduces yields of sorghum, maize, pearl millet, sugarcane and rice in thesemi-arid tropics. Germination of striga seed is induced by stimulantsexuded by roots of host and non-host plants. The objectives of this studywere to compare the ability of some host and non-host crops to inducestriga seed germination and haustoria formation as well as to confirm thesusceptibility of wheat and barley to infestation. S. hermonthica seedswere collected from Abu Haraz, Gezira State, Sudan, in 2004/2005, andtheir germination on some host and non-host crops was investigated usingroot chambers that allow observation of striga underground stages. Strigaseeds germinated with all tested crops. Besides sorghum varieties andmaize, S. hermonthica germinated, attached and developed to completestriga plants with barley and two cultivars of wheat from Sudan. This isthe first report of S. hermonthica parasitizing wheat and barley in Sudan.Use of root chambers proved that some leguminous crops weresusceptible to S. hermonthica. Chick pea (Cicer arietinum L.),phillipesera (Vigna trilobata L.), brown seed cowpea [Vigna unguiculata(L.) Walp.], hyacinth bean (Lablab purpureus L.), peas (Pisum sativumL.) pigeon pea (Cajanus cajan L.), faba bean and mung bean inducedseed germination, attachment and development of complete green strigaplants. Soybean, roselle, safflower and sunflower supported germinationand attachment of S. hermonthica, but there was no further developmentof the semi-parasitic weed. A natural brownish colouration around the